Challenges in adult vaccination. (3rd April 2018) - de Gomensoro, Eduardo; Del Giudice, Giuseppe; Doherty, T. Mark
Abstract: Life-long primary prevention interventions beginning and continuing throughout an individual's lifetime are increasingly seen as key to meeting the global healthcare challenges that accompany demographic changes – a concept referred to as "Healthy aging". In this perspective, vaccination is seen as part of a triad, together with healthy diet and exercise. Current adult vaccine coverage is lower than target vaccination rates in most developed countries, and so vaccine preventable diseases continue to present a substantial burden on health and healthcare resources, especially in older individuals. In part, this is due to lack of knowledge and understanding of the benefits of vaccination, inconsistent recommendations by providers and uncertainties about cost benefits. However, lower vaccine effectiveness in older adults plays a part, and new vaccines with novel characteristics to improve effectiveness in older adults are required. A life-course immunization approach to ensure optimal vaccine uptake across adults of all ages can be expected to reduce morbidity and mortality in later life. To achieve this, greater emphasis on public and healthcare provider education is necessary, based on appropriate economic analyses that demonstrate the overall value of vaccination. This article introduces the technical, economic, political and demographic issues that make establishing effective adult vaccination programs such a difficult, but pressing issue, and outlines some of the steps that are now being taken to address them. Key messages: Life-long preventive activities that start and continue throughout life are essential, especially as the world's population is "getting older". This "Healthy aging" approach includes not only healthy diet and physical exercise; vaccination is critical in reducing some infectious diseases and their complications. Many adults, especially older adults (who have lower immunity than younger people) develop infections such as influenza and shingles that could potentially be prevented through vaccination. This review provides a perspective on the challenges in delivering a life-course immunization program. While some vaccines are less effective in older people, newer vaccines have been developed which provide stronger and longer protection in older patients than standard existing vaccines. However, the benefits of vaccination can only be realized if the vaccines are recommended and used. For that purpose, greater education of patients and their healthcare providers is necessary. Better knowledge of vaccines and making sure that all adults are up to date with all their recommended vaccines is an essential part of "Healthy aging". This should prevent not only vaccine-preventable diseases but also reduce the risk of complications in later life.